2022
DOI: 10.1037/ocp0000303
|View full text |Cite
|
Sign up to set email alerts
|

Treat me better, but is it really better? Applying a resource perspective to understanding leader–member exchange (LMX), LMX differentiation, and work stress.

Abstract: The leader-member exchange (LMX) literature proposes that leaders tend to differentiate the quality of relationships among their followers, but it remains unclear how individual LMX and LMX differentiation (i.e., the degree to which followers' LMX quality with the same leader varies within a team) may jointly shape follower well-being such as work stress. Drawing from a resource perspective, we hypothesize that LMX differentiation reduces the beneficial effect of LMX on work stress via decreasing perceived dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 96 publications
(153 reference statements)
0
18
1
Order By: Relevance
“…Having a good relationship between leader and member within LMX theory, presents an important source for leader's psychological well-being and has an important impact on work-related stress levels (Liang et al, 2021). Leader automatically develops a relationship with each member during daily and person to person interactions which strongly influences employee engagement, work zeal and stress level (Wang & Li, 2018), yet with working from home, leader has no extensive interactions with his members or followers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Having a good relationship between leader and member within LMX theory, presents an important source for leader's psychological well-being and has an important impact on work-related stress levels (Liang et al, 2021). Leader automatically develops a relationship with each member during daily and person to person interactions which strongly influences employee engagement, work zeal and stress level (Wang & Li, 2018), yet with working from home, leader has no extensive interactions with his members or followers.…”
Section: Discussionmentioning
confidence: 99%
“…During work from home, the leader's stress increased, as there is no person to person contact between employees and directly between the leader and the employee, and the leader cannot perform other vital activities such as adapting the approach to each employee, maintaining work environment and organizational climate, which are the central part of LMX theory (Alexander, 2020;Liang et al, 2021;Wang & Li, 2018). With work from home, practicing LMX theory cannot reach its full potential, furthermore, there is a risk of deteriorating relationships, trust and organizational climate (Alexander, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown that leadership behavior has an important impact on LMX quality [ 37 , 38 , 39 ]. The influence of voice endorsement on LMX can be explained from two aspects: First, voice endorsement helps employees to judge whether their cognition of organizational problems is accurate through leader’s supportive attitude so as to reduce organizational conflicts caused by individual role ambiguity, thus forming a high-quality LMX relationship; second, the social exchange theory holds that reciprocal norms are the core principle of LMX, and the mutual feedback based on each other’s contribution is the basis for the maintenance and development of the exchange relationship [ 40 , 41 ]. When individuals get the benefits provided by others, they will correspondingly give back the necessary benefits to the benefit providers.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%